Rotigotine patch prescription in inpatients with Parkinson's disease: evaluating prescription accuracy, delirium and end-of-life use. (3rd December 2020) - Ibrahim, Hussein; Woodward, Zoe; Pooley, Jennifer; Richfield, Edward William
Abstract: Background: Rotigotine patch, a trans- dermal dopamine agonist, is used acutely to replace oral dopaminergic medications for inpatients with Parkinson's disease where enteral routes are no longer available, and is also an option in end-of-life care where patients can no longer swallow. Concerns regarding acute use of Rotigotine include difficulty achieving dopaminergic equivalence, promotion of delirium/hallucinations and promotion of terminal agitation. Objective: our objectives were to establish: (i) accuracy of Rotigotine prescribing, (ii) rates of delirium/hallucinations and (iii) rates of terminal agitation. Method: we retrospectively evaluated the use of Rotigotine in an inpatient population at a UK teaching hospital. Prescriptions between January 2018 and July 2019 were identified and inpatient records were analysed. OPTIMAL Calculator 2 was used as a gold standard for assessing conversion of oral dopaminergic medication to Rotigotine. Results: a total of 84 inpatients were included. 25 (30%) patients were prescribed the recommended dose of Rotigotine; 31 (37%) higher and 28 (33%) lower than recommended. A total of 15 of 41 (37%) patients with dementia and 22 of 49 (45%) patients with delirium before initiation of Rotigotine inappropriately received the higher dose; 20 (24%) patients developed new/worsening delirium and 8 (10%) patients developed new/worsening hallucinations; and 59 (70%) patients were dead at time of evaluation, of these 40 (68%) died in hospital, 10 (25%) of whom experienced terminal agitation. Conclusions: acute conversion of oral dopaminergic medication to trans- dermal Rotigotine patch remains problematic despite the availability of validated tools. Inappropriate dosing may precipitate or worsen delirium/hallucinations. Use at end-of-life requires further evaluation.